2017
DOI: 10.2460/ajvr.78.12.1380
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of blood cell counts on multiple-electrode impedance aggregometry in dogs

Abstract: OBJECTIVE To assess the effect of decreased platelet and WBC counts on platelet aggregation as measured by a multiple-electrode impedance aggregometer in dogs. ANIMALS 24 healthy dogs. PROCEDURES From each dog, 9 mL of blood was collected into a 10-mL syringe that contained 1 mL of 4% sodium citrate solution to yield a 10-mL sample with a 1:9 citrate-to-blood ratio. Each sample was then divided into unmanipulated and manipulated aliquots with progressively depleted buffy-coat fractions such that 2 to 3 blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…where a wider range of cell counts was evaluated, 3 AUC was significantly associated with the WBC count. Because all blood samples for this study were obtained from healthy dogs, no severe hematologic abnormalities were present.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…where a wider range of cell counts was evaluated, 3 AUC was significantly associated with the WBC count. Because all blood samples for this study were obtained from healthy dogs, no severe hematologic abnormalities were present.…”
Section: Discussionmentioning
confidence: 96%
“…The platelet count was an exception to this rule, but all platelet counts were >100 000/µL. Previous work indicates that platelet aggregation is not affected if the platelet count is above 50 000/µL 3 . Blood smears were prepared from the blood in EDTA prior to sample manipulation and evaluated by a single investigator (CAL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole blood impedance platelet aggregometry (Multiplate) is a specialized assay that can be used to assess platelet function in dogs . Over the past several years, veterinary studies in dogs have used this assay, and it is being used clinically with an increasing frequency . This method uses anticoagulated whole blood and platelet agonists that stimulate platelets to aggregate.…”
Section: Whole Blood Impedance Platelet Aggregometry Showing the Areamentioning
confidence: 99%
“…The area under the curve (AUC) is the standard measurement reported that describes platelet responses to different agonists . Arachidonic acid (AA) and adenosine diphosphate (ADP) are two agonists that are used frequently in veterinary medicine . To perform the assay, reagents are reconstituted according to the manufacturer's (Multiplate 5.0 Analyzer; Diapharma Group Inc., West Chester, OH, USA) recommendations and can be stored in aliquots at 2‐8°C for 24 hours or ≤−20°C for 4 weeks.…”
Section: Whole Blood Impedance Platelet Aggregometry Showing the Areamentioning
confidence: 99%